2021
DOI: 10.3389/fcvm.2021.647720
|View full text |Cite
|
Sign up to set email alerts
|

The Incremental Prognostic Value of the Clinical Residual SYNTAX Score for Patients With Chronic Renal Insufficiency Undergoing Percutaneous Coronary Intervention

Abstract: Background: The residual SYNTAX score (RSS) is considered a powerful prognostic indicator for determining a reasonable revascularization strategy in patients undergoing percutaneous coronary intervention (PCI), but the absence of clinical parameters is one of the limitations of RSS, especially in the chronic renal insufficiency (CRI) comorbidity setting. The present work aimed to investigate the incremental prognostic value of clinical residual SYNTAX score (CRSS) compared with RSS in CRI cases after PCI.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Mounting epidemiological evidence suggests that insulin resistance constitutes an independent prognostic predictor in CAD [16], but insulin resistance or its surrogate marker has not been included in any risk prediction tools, such as the GRACE score or the SYNTAX score. Previous studies have shown that prediction models combining anatomical and clinical factors such as the SYN-TAX II score and clinical residual SYNTAX score could improve the discriminative ability for a better risk assessment [17][18][19]. One of our previous studies also highlighted that adjustment of the residual SYNTAX score by the TyG index significantly improves the predictive accuracy for adverse cardiovascular events in patients with type 2 diabetes mellitus undergoing PCI [11].…”
Section: Discussionmentioning
confidence: 83%
“…Mounting epidemiological evidence suggests that insulin resistance constitutes an independent prognostic predictor in CAD [16], but insulin resistance or its surrogate marker has not been included in any risk prediction tools, such as the GRACE score or the SYNTAX score. Previous studies have shown that prediction models combining anatomical and clinical factors such as the SYN-TAX II score and clinical residual SYNTAX score could improve the discriminative ability for a better risk assessment [17][18][19]. One of our previous studies also highlighted that adjustment of the residual SYNTAX score by the TyG index significantly improves the predictive accuracy for adverse cardiovascular events in patients with type 2 diabetes mellitus undergoing PCI [11].…”
Section: Discussionmentioning
confidence: 83%
“…Clinical prognostic variables have been combined with the anatomical SXscore to increase the its accuracy to guide the choice between PCI and CABG for patients with multivessel coronary disease, such as the logistic clinical SYNTAX score (31)(32)(33)(34)(35), the CABG SYNTAX Score (36,37), the SYNTAX score II (38)(39)(40)(41), the SYNTAX score III (42,43), the residual SYNTAX score (44), and the clinical residual SYNTAX score (45). These more complex scores derived from the SYNTAX score have not gained practical application as well, and some of them have been less effective to predict outcomes than other functional predictors, such as the fractional flow reserve (FFR) (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…The glomerular filtration rate was estimated for all patients utilizing the simplified Modification of Diet in Renal Disease method. As per our previous description, a subset of 2468 patients exhibited an assessed glomerular filtration rate (eGFR) of 90 mL/min/1.73 [ 10 , 11 ]. Among them, 1161 patients with left main and/or three-vessel CAD were present.…”
Section: Methodsmentioning
confidence: 99%